Patient with dysexecutive syndrome after brain injury - case report - Patrycja Daniela Łanowy; Jarosław Szczygieł (Kazimierz Wielki University, 2019)
Traumatic brain injury is usually caused by multiple kinds of falls, violence with head injury or traffic incidents. In this article, we describe the case of a 51-years-old patient with craniocerebral trauma, requiring the introduction into a pharmacological coma. The patient was diagnosed with a hemorrhagic contusion of the frontal lobes with numerous intracerebral hematomas, significant local cerebral edema, hematomas at the cerebral frontal and temporal lobes, subarachnoid bleeding in the cerebellar tent. After the brain injury patient demonstrates features of the dysexecutive syndrome, her disability on the Rankin's scale was rated with 5 grade. Thanks to properly selected drug therapy and conducting properly targeted rehabilitation, the patient's condition improved spectacularly, and the patient gained independence.